Sexualities in anthropology a reader - Lyons, Andrew P. 1944- (Andrew Paul).; Lyons, Harriet D. 1943-; Weston, Kath 1958- (Chichester, West Sussex, England Wiley-Blackwell, 2011)
"This thought-provoking new collection, Sexualities in Anthropology: A Reader offers insights into the diversity of human social beliefs and practices relating to sexuality in different times and in different cultures around the world. Substantial editorial introductions set each Part in context of the field, providing readers helpful background and explanatory notes. Presents a comprehensive collection of key historical and current readings in the social anthropology of sexuality Includes literature on both heterosexualities and same-sex sexualities Explores the key works and major debates of prominent scholars in the field, such as Mead, Malinowski, Newton , Herdt, and others Introduces readers to major theoretical developments ("essentialist" and "constructionist" positions)"--Provided by publisher.
"Shedding important new light on a subject as old as humanity itself, Sexualities in Anthropology: A Reader presents a comprehensive collection of historical and current readings in the social anthropology of sexuality. Succinct and revealing excerpts from key figures in the history of anthropology about sexualities, morality, and the family are featured. The most recent literature on both heterosexualities and same-sex sexualities is also included, as well as material on past and present controversies, including Derek Freeman's famous attack on Margaret Mead's writings on sexual freedom in Samoa; the notion of "primitive" promiscuity in the 19th and early 20th centuries; concerns for the practice of clitoridectomy and other forms of "genital cutting;" the discussion of homosexualities in different cultures; and the meaning of love. Thought-provoking and always fascinating, Sexualities in Anthropology: A Reader offers keen insights into the diversity of human social beliefs, practices, and interactions relating to human sexual behavior around the world"-- Provided by publisher.
Machine generated contents note: INTRODUCTION: PROBLEMS IN WRITING ABOUT SEX IN ANTHROPOLOGY -- 1. The bubble, the burn, and the simmer: introduction: locating sexuality in social science (Kath Weston) -- PART I: SEX, RACE AND GENDER IN ANTHROPOLOGICAL HISTORY -- 2. Which Bodies Matter? Feminism, Poststructuralism, Race and the Curious Theoretical Odyssey of Hottentot Venus (Zine Magubane) -- PART II: PRIMITIVE PROMISCUITY AND MATRIARCHAL THEORY ('OVERSEXED SAVAGES') -- 3. Origin of the Family, Private Property and the State (Frederick Engels) -- PART III: AGAINST PRIMITIVE PROMISCUITY (FEAR OF SEX) -- 4. Irregular Connections - on Westermarck, Ellis and Crawley, "The Reconstruction of Primitive Sexuality at the Fin de Siecle (Andrew Lyons and Harriet Lyons) -- 5. Studies in the Psychology of Sex (Havelock Ellis) -- 6. The Mystic Rose, Selections (Ernest Crawley) -- PART IV: EARLY WORK ON HOMOSEXUALITIES -- 7. Richard Burton's Arabian Nights: Terminal Essay -- 8. Origin and Development of the Moral Ideas: Selections (Edvard Westermarck) -- 9. Hermaphrodism among gods and mortals (Edward Carpenter) -- 10. The Zuni Lamana (Elsie Clews Parsons) -- PART V: HETEROSEXUAL FREEDOMS - ELSEWHERE -- 11. Extracts from The Sexual Life of Savages (Bronislaw Malinowski) -- 12. Extracts from Coming of Age in Samoa (Margaret Mead) -- 13. Extract from Premarital Pregnancy and Native Opinion (Isaac Schapera) -- PART VI: SEXUAL REPRESSION - A TEST CASE -- 14. Sex and Repression in an Irish Folk Community (John Messenger) -- PART VII: VIRGIN BIRTH -- 15. The Sexual Life of Savages in North-Western Melanesia, Extracts (Bronislaw Malinowski) -- 16. Coming into Being Among the Australian Aborigines (Ashley Montagu) -- 17. Virgin Birth: Extracts (Edmund Leach) -- PART VIII: THE ATTACK ON MARGARET MEAD -- 18. Sex and Hoax in Samoa (Derek Freeman) -- 19. Sexual Morality in Samoa and its Historical Transformations, From A Polymath (Penelope Schoeffel) -- 20. Virginity and the History of Sex in Samoa (Paul Shankman) -- PART IX: GENITAL CUTTING -- 21. Genital Cutting: The Past and Present of a Polythetic (Harriet Lyons) -- PART X: GAY, BISEXUAL, LESBIAN, TRANSGENDER -- 22. 'Role Models' (Esther Newton) -- 23. Notes and Queries on Sexual Excitement in Sambia Culture (Gilbert Herdt) -- 24. Causing a Commotion: Public Scandal as Resistance Among Brazilian Transgendered Prostitutes (Don Kulick) -- 25. Between Religion and Desire, Being Muslim and GAY in Indonesia (Tom Boellstorff) -- 26. The Semiotics of Transgendered Sexual Identity in the Thai Print Media (Megan Sinnott) -- 27. The Categories Themselves (David Valentine) -- PART XI: HETEROSEXUALITY TODAY -- 28. A Good Spouse is Hard to Find: Marriage, Spouse Exchange, and Infatuation Among the Copper Inuit (Pamela R. Stern and Richard G, Condon) -- 29. Love and the Risk of HIV (Daniel Jordan Smith) -- 30. Beyond Pain, Towards Pleasure in the Study of Sexuality in Africa (Rachel Spronk).
Includes bibliographical references and index.
Keywords: Sex customs -- Cross-cultural studies